1999
DOI: 10.1115/1.429643
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Characteristics Downstream of Bileaflet Aortic Valve Prostheses

Abstract: This study was focused on a series of in vitro tests on the turbulent flow characteristics of three bileaflet aortic valves: St. Jude Medical (SJM), CarboMedics (CM), and Edwards Tekna (modified Duromedics, DM). The flow fields of the valves were measured in a pulsatile flow model with a laser-Doppler anemometer (LDA) at the aortic sinus area downstream of the valves. The heart rate was set at 70 beats per minute, the cardiac output was maintained at 5 liters per minute, and the aortic pressure wave forms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
130
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 28 publications
11
130
0
Order By: Relevance
“…According to these results, the peak membrane tension induced by the Kolmogorov eddy is nearly independent of the eddy length scale. Figure 9 shows the corresponding results for microscale eddies with velocity scales determined from the turbulent energy spectrum of Liu et al 21 .…”
Section: Application To Turbulent Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these results, the peak membrane tension induced by the Kolmogorov eddy is nearly independent of the eddy length scale. Figure 9 shows the corresponding results for microscale eddies with velocity scales determined from the turbulent energy spectrum of Liu et al 21 .…”
Section: Application To Turbulent Flowmentioning
confidence: 99%
“…8,14,21,33 However, the Reynolds stress is an averaged momentum flux which contains no information about the size of flow structures in turbulence, and therefore cannot fully characterize the mechanical environment of individual cells. It has been shown that the Reynolds stress is an inaccurate indicator of true viscous stresses in turbulent flow of a homogeneous fluid, 13,17 and of flowinduced stress on blood cells suspended in turbulent flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has also been argued that the possible error induced by the SGS model would be less pronounced at peak flow conditions due to the more developed turbulence field. 35 By only simulating steady LES the computational cost could be reduced substantially compared to a pulsatile counterpart, where as much as 20 cardiac cycles have been proven necessary to obtain sufficient phase average results (see Online Resource). In a combined framework, accuracy and speed should be enhanced in order to approach clinical practice.…”
Section: Ma Ps MD Es Ldmentioning
confidence: 99%
“…Geometry and dynamics of artificial occluders promote abnormal features such as jets, separation, and vortex shedding, which can subject cell trajectories to prolonged or intermittent exposure to large shearing forces 5,6 . It has been suggested that flow structures in these fields are effective at scales down to tens of µm 7,8 or mathematical models 15,[19][20][21][22] . Since cellular response to stress is dependent on history, such models must be integrated over the Lagrangian trajectory of a cell through the flow field of a given device in order to predict flow-induced blood damage.…”
Section: Introductionmentioning
confidence: 99%